PEMANFAATAN KAWASAN DI SEKITAR CAGAR ALAM PULAU DUA SERANG OLEH TIGA JENIS KUNTUL - Elfidasari, Dewi (E-Journal Widya Kesehatan dan Lingkungan, 2005)
The objective of this study is to determine the regional use of Cagar Alam Pulau Dua (CAPD) natural reservation by three species of herons (Casmerodius albus, Egretta garzetta, Bubulcus ibis) that lived in Cagar Alam Pulau Dua Serang, Banten province. Casmerodius albus and Egretta garzetta used the mudflat, fisheries and rice-fields around CAPD as feeding location. Bubulcus ibis used rice-field and grassland as feeding location. The preference of Casmerodius albus to feeding in mudflad is (x2 = 21691.29; db=2, Î± = 0.01). Egretta garzetta have preference for feeding in fisheries ( x2 = 18221.27; db=2, Î± = 0.01) and the preference for Bubulcus ibis to feed in grassland is ( x2 =27.57; db=1, Î± = 0.01)